Reverdin-Isham technique with and without fixation: preliminary results - Sato, Aleksei Dickow; Nakato, Ronaldo Muramoto; Bolsi, Bruno Cerutti; Zigovski, Thiago Pavani; Silva, João Luiz Vieira da (Scientific Journal of the Foot & Ankle, 2018)
Objective: This study evaluated the radiographic results of the traditional minimally invasive percutaneous Reverdin-Isham surgical technique for hallux valgus treatment using the American Orthopaedic Foot and Ankle Society (AOFAS) score and compared this result with a proposed modification involving additional osteosynthesis with a cannulated screw. Methods: We retrospectively assessed 22 feet across 15 patients with mild to moderate hallux valgus. All patients underwent surgical treatment using the Reverdin-Isham technique. Eleven feet were fixed with 2.4- or 2.7-mm cannulated screws. A single orthopaedic surgeon performed these procedures between January 2014 and June 2016. The metatarsophalangeal (MTP) angle and intermetatarsal angle (IMA) were evaluated using radiographs, and the AOFAS score was applied before surgery and 90 days after. Results: An improvement was found in the parameters evaluated in both groups, with significant differences shown between the pre- and post-procedure follow-up assessment. No significant difference was found between the groups with regard to fixation; however, the scores were slightly higher for the group where osteosynthesis was used. Conclusion: The Reverdin-Isham procedure is effective and safe for correcting mild to moderate hallux valgus and additional fixation presented with promising results, although without significant difference. Additional studies with larger samples and longer follow-up times are needed to define the role that additional screw fixation plays in the overall scope of treatment. Level of Evidence IV; Therapeutic Studies; Case Series.